2021
DOI: 10.1177/1368430221990082
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and psychological distress among immigrants to Canada: The mediating role of bicultural identity orientations

Abstract: Bicultural identity orientations have rarely been examined in relation to both perceived discrimination and psychological distress. Furthermore, these constructs have usually been studied in isolation, but their intersection is essential for understanding intercultural relations in multicultural societies. Using cross-sectional data from 1,143 Canadian undergraduate students from immigrant families, this study explored the relationship between perceived discrimination and psychological distress, and how bicult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 85 publications
5
21
3
Order By: Relevance
“…Thus, it is possible that more advanced intercultural abilities help people to avoid situations where discrepancies between the two groups arise and, as a result, to encounter fewer occasions where culturally stressful encounters (e.g., discriminatory behavior) and events are likely to occur. In contrast, our findings also indicated that an AIS may be less functional for Hispanic college students and support prior work suggesting that greater discomfort with managing multiple cultural identities may predict poor psychological adjustment (Firat et al, 2022;Ward et al, 2018Ward et al, , 2021. In the present sample, it is possible that students who more frequently used an AIS perceived less congruence between their two cultures, and therefore tended to experience greater amounts of cultural stress.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is possible that more advanced intercultural abilities help people to avoid situations where discrepancies between the two groups arise and, as a result, to encounter fewer occasions where culturally stressful encounters (e.g., discriminatory behavior) and events are likely to occur. In contrast, our findings also indicated that an AIS may be less functional for Hispanic college students and support prior work suggesting that greater discomfort with managing multiple cultural identities may predict poor psychological adjustment (Firat et al, 2022;Ward et al, 2018Ward et al, , 2021. In the present sample, it is possible that students who more frequently used an AIS perceived less congruence between their two cultures, and therefore tended to experience greater amounts of cultural stress.…”
Section: Discussionsupporting
confidence: 79%
“…This study provides further evidence that hybridising, a characteristic process of the HIS, leads to more favourable well-being outcomes in terms of fewer psychological symptoms and greater life satisfaction. This is in accordance with previous research where HIS was linked to greater life satisfaction and fewer psychological symptoms (Ward et al, 2018;Schwartz et al, 2019;Firat & Noels, 2021).…”
Section: Hybridisers and Highly Dual Processorssupporting
confidence: 93%
“…In terms of different configurations of HIS and AIS being related to cultural identity outcomes, given the previous research (Ward et al, 2018), it is likely that the group with predominant use of HIS would be associated with the greatest level of cultural identity consolidation and the group with the predominant use of AIS would be associated with the greatest level of cultural identity conflict (Ward et al, 2018;Schwartz et al, 2019;Firat & Noels, 2021). Regarding the group who adopts both HIS and AIS (dual processors), Schwartz et al's (2019) research found that well-being positively correlated with HIS and negatively correlated with AIS, so as HIS is thought to relate to greater cultural identity consolidation and AIS to greater cultural identity conflict, the group characterised by endorsing both HIS and AIS will be expected to display moderately high levels of cultural identity consolidation, in between the other two groups.…”
Section: Cultural Identity Styles Identity Outcomes and Well-beingmentioning
confidence: 96%
“…For Multicultural people, discrimination is associated with different orientations toward one's Multicultural identity. More frequent discrimination was associated with a less harmonious and complementary Multicultural identity (Firat & Noels, 2021;Huynh et al, 2018). However, some work found no association between discrimination and identity harmony among first-generation Multicultural people (Huynh et al, 2018).…”
Section: Identity Correlates Of Discriminationmentioning
confidence: 97%
“…Recognition of frame switching may lead some Multicultural people to experience compartmentalization or alternation, the experience of keeping one's cultural identities separate and contextspecific (Yampolsky et al, 2016; also see, Downie et al, 2006). However, there is debate over the extent to which frame switching and alternating identities are bound versus independent, with some researchers pointing to instances of highly integrated Multicultural people still frame switching and the moderating role of identity integration and authenticity on the relative positive versus negative outcomes of frame switching (Firat & Noels, 2021;Hong & Schmidt, 2021;Meca et al, 2019;Szabó et al, 2020;Ward et al, 2021).…”
Section: Alternation and Frame Switchingmentioning
confidence: 99%